Management of Poor Responders in IVF: Is There Anything New?. (20th July 2014) - Ubaldi, Filippo; Vaiarelli, Alberto; D'Anna, Rosario; Rienzi, Laura
Abstract : Despite the fact that in the last two decades an enormous number of papers on the topic of poor ovarian response have been published in the literature, so far it has been impossible to identify any efficient treatment to improve the ovarian response and the clinical outcome of this group of patients. The incidence of poor ovarian responders among infertile women has been estimated at 9–24% but according to recent reviews, it seems to have slightly increased. The limitation in quantifying the incidence of these patients among the infertile population is due to the difficulty of a clear definition in literature. A recent paper by the Bologna ESHRE working group on poor ovarian response has been the first real attempt to find a common definition. Current literature proposes new risk factors which could be the cause of a reduction in ovarian reserve, which also includes genetic factors. This represents the first necessary step towards finding applicable solutions for these patients. To date, there is a substantial lack of literature that identifies an ideal protocol for these patients. The use of the "Bologna criteria" and the introduction of long acting gonadotropin in clinical practice have given rise to new promising stimulation protocols for this group of patients.